Оптимизация топологий сетей на кристалле - Романов, А. Ю. (НТУ "ХПИ", 2011)
Рассмотрены классические топологии построения СтНк и их основные достоинства и недостатки. Предложен и реализован программно алгоритм поиска оптимальных топологий в соответствии с ограничениями по диаметру и максимальной степени вершин с оптимизацией по количеству соединений и среднему расстоянию. Синтезированы оптимальные топологии для количества вершин от 6 до 10.

The main advantages and disadvantages of classical topologies of networks on chip (NoC) are considered. The algorithm for finding optimal topologies in accordance with the restrictions on the diameter and maximum degree of optimization on the number of connections and the average distance proposed and implemented in software. The optimized topologies for the NoCs with the number of nodes between 6 and 10 synthesized.
Optimization of topologies of networks on chip
Keywords: электроника; вычислительный модуль; неориентированный связный граф; тороидальная сеть; network on chip; optimal topology